Early cracking orientation under high stress gradients: The fretting case. (July 2017) - Araújo, J.A.; Almeida, G.M.J.; Ferreira, J.L.A.; da Silva, C.R.M.; Castro, F.C.
Highlights: Early cracking orientation in the fretting problem was studied. The high stress gradients cause a difficulty to modeling attempts. Conventional critical distance/plane methods may yield inconsistent cracking directions. The use of average stress quantities over a critical direction is proposed. Better cracking orientation estimates were obtained. Abstract: Many fretting contacts experience a rapid variation of the magnitude and relative contribution of the stress components away from the surface. This feature of the fretting problem poses an additional difficulty for the modeling of the early cracking orientation. In this work, critical plane approaches associated with a process zone are evaluated by taking into account the fretting crack behavior observed in two different steels. The results show that the conventional approaches may provide inconsistent cracking directions. A new method for early cracking orientation prediction is developed by employing the average values of the normal and shear stresses along a critical direction. This method is simpler to implement and improves the estimates when compared to the other approaches.